Friend or foe? The role of solvents in non-triplet, intraligand charge transfer sensitization of lanthanide(iii) luminescence. Issue 78 (4th August 2016) - Lo, Wai-Sum; Wong, Wing-Tak; Law, Ga-Lai
Abstract : A comprehensive photophysical and solvatochromic study is conducted to evaluate the luminescence properties of our Eu(iii ), Sm(iii ) and Yb(iii ) complexes. Abstract : Sensitization of lanthanide luminescence in the visible and near infra-red (NIR) region was achieved via a non-triplet energy transfer pathway by long-wavelength excitation of an intraligand charge transfer (ILCT) band of a diethylamino-based ligand system. A comprehensive photophysical and solvatochromic study is conducted to evaluate the luminescence properties of our Eu(iii ), Sm(iii ) and Yb(iii ) complexes. The effects of solvent coordination and solvent quenching on lanthanide luminescence were studied in detail and efforts were also devoted into examining the ambiguous energy transfer mechanism of Yb(iii ) sensitization.